TABUIK PARIAMAN DALAM PERAYAAN MUHARRAM (Pendekatan Sosiologi Seni) - Yulimarni Yulimarni; Anin Ditto (Institut Seni Indonesia Padangpanjang, 2022)
Tabuik is a work of decorative art that is formed on an aesthetic concept and is the main object for the implementation of the Muharram celebration in Pariaman City. The activity is held once a year. This study aims to examine the Pariaman tabuik from the perspective of the sociology of art by using the theory of Vera L. Zolberg. This research uses qualitative research and is analysed descriptively. Data was obtained through observation, interviews, literature study, and documentation. The data were analyzed through three stages, namely identification, classification, and interpretation. The results show that tabuik is a cultural artefact whose existence is very important in the celebration of Muharram and is formed due to social processes. Initially, the tabuik celebration was carried out as a sacred ceremony and contained sacred values. Now the implementation of Tabuik is more directed to the value of entertainment or tourism. All of that, of course, cannot be separated from the role of government institutions, tabuik artists, and supporting communities as art constructions. So that tabuik can live and thrive in Pariaman City until now.